Sustainable Growth for Small and Medium-Sized Enterprises: Interpretive Structural Modeling Approach - Runtuk J.K.; Ng P.K.; Ooi S.Y.; Purwanto R.; Nur Chairat A.S.; Ng Y.J. (MDPI, 2024)
Small and medium-sized enterprises (SMEs) are constantly under pressure to grow. This pressure forces everyone involved to think about how best to run their business. Although there is much research on SME growth, previous research is fragmented and only addresses internal or external enablers. This study aims to construct an interaction model for all enablers that promote sustainable SME growth. An interpretive structural modeling (ISM) analysis is conducted to formulate an interaction model of enablers for SME growth. The results show that both internal and external enablers are crucial for SME growth. This study shows that the following internal enablers that are interrelated and strongly influence SME growth are MS (managerial skills), EO (entrepreneurial orientation), and OwS (ownership structure). In addition, external enablers such as CIL (customer involvement and location) and GS (government support) also play an important role in improving the performance of other factors for SME growth. In addition, this study also provides a guide for formulating strategies for SME sustainability. Effective policy formulation must be based on a correct understanding of the interdependence between enablers as a unified model of interaction. The interaction between the enablers highlighted and the level of the model would be helpful to all shareholders in finding appropriate strategies for SME growth. 2023 by the authors.